Implementasi Program Sunnah Culture melalui KKN dalam Membangun Budaya Kerja Islami pada UMKM Laundry Syari Kampung Maghfirah - Sarah Rifat Al Hawari; Hera Rachmadini; Lely Nuralfi Laili; Sakho’ Labiibah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the implementation of the Sunnah Culture program in building an Islamic work culture at Laundry Syari Kampung Maghfirah. The program was carried out through the Kuliah Kerja Nyata II (KKN II) activities by implementing several practices, such as playing Qur’anic murottal, habituating prayers before work, performing dhuha prayer, and applying a dhuha checklist. This study employed a qualitative approach using the Participatory Action Research (PAR) method. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results showed that the implementation of the Sunnah Culture program had a positive influence on the formation of an Islamic work culture, particularly in creating a calmer, more conducive, and spiritually nuanced work environment. In addition, the program strengthened the habituation of worship and workers’ spiritual awareness within the workplace. However, several programs were not implemented optimally due to limited implementation time and the high operational activities of the laundry business. Overall, the implementation of the Sunnah Culture program contributed positively to the development of an Islamic work culture, although consistency and sustainability are still needed for its implementation.   Keywords: Sunnah Culture, Islamic Work Culture, KKN, Laundry Syari